Water Balance and Desiccation Tolerance of the Invasive South American Tomato Pinworm - Tarusikirwa, Vimbai L; Cuthbert, Ross N; Mutamiswa, Reyard; Gotcha, Nonofo; Nyamukondiwa, Casper (Entomological Society of America and Oxford University Press, 2022)
Temperature and dehydration stress are two major co-occurring environmental stressors threatening the physiology, biochemistry, and ecology of insects. As such, understanding adaptive responses to desiccation stress is critical for predicting climate change impacts, particularly its influence on insect invasions. Here, we assessed water balance and desiccation resistance of the invasive Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae), and infer how eco-physiology shapes its niche. We measured basal body water and lipid content, water loss rates (WLRs), and desiccation resistance in larvae (second to fourth instars) and adults. Body -water, -lipid, and WLRs significantly varied across life stages. Second instars recorded the lowest while fourth instars exhibited the highest body water and lipid content. Adult body water and lipid content were higher than second and third instars and lower than fourth instars while proportion of body water and lipid contents were highest in adults and second larval instars respectively. Water loss rates were significantly highest in fourth-instar larvae compared to other life stages, but differences among stages were less apparent at longer exposure durations (48 h). Desiccation resistance assays showed that second instars had greatest mortality while fourth-instar larvae and adults were the most desiccation tolerant. Our results show that T. absoluta fourth-instar larvae and adults are the most resilient developmental stages and potentially contribute most to the invasion success of the pest in arid environments. Incorporation of these species-specific eco-physiological traits in predictive models can help refine invasive species potential spread under changing climates.